Analysis of Spontaneous Movements in Infants With Torticollis. Issue 1 (4th January 2022) - Kahraman, Aysu; Büğüşan Oruç, Sema; Erdoğan, Derya; Mutlu, Akmer
Abstract : This study aimed to investigate whether the movements and posture of 3- to 5- month-old infants with torticollis differ from those of infants without torticollis and to determine the relationship between clinical characteristics and Motor Optimality Score. Abstract : Purpose: This study aimed to investigate whether the movements and postures of 3- to 5-month-old infants with torticollis differ from those of infants without torticollis and to determine the relationship between clinical characteristics and the Motor Optimality Score (MOS) in torticollis. Methods: Participants were 40 infants with torticollis and 40 infants developing typically without torticollis. The infants were evaluated with detailed general movement assessment. Results: There were significant differences in the MOS and subcategory scores for age-adequate movement repertoire and observed postural patterns between groups. Clinical characteristics were not related to the reduction in the MOS. Conclusions: Infants with torticollis have differences in movements and postures at 3 to 5 months of age compared with controls. Strategies supporting the movement repertoire of infants with torticollis can be added to rehabilitation programs for infants with the lower MOS to optimize their motor development.